2009
DOI: 10.1177/1091581809333138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atrazine and Fenoxaprop-Ethyl on Capacitation and the Acrosomal Reaction in Boar Sperm

Abstract: Atrazine is a herbicide of the chloro-s-triazine family. It inhibits photosynthesis in plants and is an endocrine disruptor, but its effects on human health are controversial. Fenoxaprop-ethyl, an aryloxy phenoxyalkanoic acid herbicide, inhibits the biosynthesis of fatty acids and provokes depolarization of membranes. The aim of this study is to evaluate the in vitro effects of both herbicides on capacitation, spontaneous acrosome reaction (SAR) and progesterone-induced acrosome reaction (PIAR) in boar sperm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
0
8
0
2
Order By: Relevance
“…AR is essential not only for sperm passage through the zona pellucida but also for membrane fusion between the sperm and egg [24], therefore atrazine will impact the crab's fertilization. Whereas in the previous study, there was a different conclusion: the same herbicide could increase significantly AR in boar spermatozoa [25]. The authors considered that atrazine accelerate AR via plasma membrane destabilization.…”
Section: Resultsmentioning
confidence: 93%
“…AR is essential not only for sperm passage through the zona pellucida but also for membrane fusion between the sperm and egg [24], therefore atrazine will impact the crab's fertilization. Whereas in the previous study, there was a different conclusion: the same herbicide could increase significantly AR in boar spermatozoa [25]. The authors considered that atrazine accelerate AR via plasma membrane destabilization.…”
Section: Resultsmentioning
confidence: 93%
“…Unfortunately, its indiscriminate use has damaged the environment and even humans. Mammals are exposed to FE through the food chain, and it might harm their fertility or reproduction …”
Section: Introductionmentioning
confidence: 99%
“…However, before spermatozoa become able to undergo the acrosome reaction, they must undergo capacitation, a process without which they do not become functionally competent, and little is known about the potential effects of pesticides in this process. Apart from p,p'-DDE and atrazine, which were able to suppress capacitation markers in human and boar sperm (Maravilla-Galván et al 2009, Tavares et al 2015, and fenoxaprop-ethyl, which was found to increase capacitation (MaravillaGalván et al 2009), to our knowledge no other in vitro studies have been performed. Nevertheless, the concentrations used to obtain such findings cannot be considered environmentally relevant.…”
Section: Pesticidesmentioning
confidence: 94%
“…Fenoxaprop-ethyl, atrazine, and organophosphates such as parathion and its active metabolite paraoxon were also found to induce the acrosome reaction in vitro (Contreras et al 1999, Maravilla-Galván et al 2009). However, before spermatozoa become able to undergo the acrosome reaction, they must undergo capacitation, a process without which they do not become functionally competent, and little is known about the potential effects of pesticides in this process.…”
Section: Pesticidesmentioning
confidence: 99%